The Effect of Liquidity, Liquid Assets, and Non-Performing Loans on Financial Performance with Cost Efficiency As A Moderation Variable Banking Listed on The Indonesia Stock Exchange - Marjohan, Masno (MIX: JURNAL ILMIAH MANAJEMEN, 2024)
Objectives: This investigation aimed to ascertain the influence of Liquidity, Capital Adequacy, and Non-Performing Loans on Financial Performance while considering the moderating role of Cost Efficiency. Methodology: This study utilizes secondary data collected through purposive sampling. 100 samples were selected based on specific criteria over 5 time periods using the EViews testing tool. The data was analyzed using Panel Data Regression with Moderating Regression Analysis. Finding: Liquidity and capital adequacy positively impact financial performance, while non-performing loans have no significant effect. Cost efficiency strengthens the positive effects of liquidity and capital adequacy but not of non-performing loans.Conclusion: Enhancing financial performance is crucial for any organization, and liquidity and capital adequacy play a vital role in achieving this goal. These factors have been proven to have a favorable impact on the overall financial health of a company. Conversely, non-performing loans appear to have a negligible impact on financial performance. However, cost efficiency can further strengthen the positive effects of liquidity and capital adequacy, but it does not have the same impact on non-performing loans. Hence, focusing on maintaining high levels of liquidity and capital adequacy, along with improving cost efficiency, can greatly contribute to enhancing financial performance.